COLOR AND APPEARANCE: रंग एवं रसाभिव्यक्ति - Tyagi, Namita (International Journal of Research -GRANTHAALAYAH, 2014)
The purpose of human life lies in action or creation. Life without it does not exceed zero. In an artwork, humans express their experiences only on the basis of certain picture elements and aesthetic principles. The process of embellishing this form is given the noun of art. The language of art is full of emotion as a result of heart feeling. Emotion means feeling, emotion, impulse, impulse, emotion, desire, nature and experience of satire etc. This experience affects our soul by entering our inner mind and brain through our senses. This sentiment flows in our conscience in the form of happiness and sorrow and situations appear in different forms. These sentiments are divided into the category of rasa in the Indian ancient scriptures. These rasa are manifested in various forms in the works of the artist and by the graceful appearance of colors which delight the viewer. मानव जीवन का उद्देश्य क्रियाशीलता अथवा निर्माण में निहित है। इससे रहित जीवन शून्य से अधिक नहीं होता। एक कलाकृति में मानव अपने अनुभवों को निश्चित चित्र तत्वों एवं सौन्दर्य सिद्धान्तों के आधार पर ही अभिव्यक्ति करता है। इस रूप सजृन की प्रक्रिया को कला की संज्ञा प्रदान की जाती है। हृदय अनुभूति के परिणाम स्वरूप ही कला की भाषा भावों से परिपूर्ण है। भाव का अर्थ होता है, भावना, उद्वेग, आवेग, संवेग, उन्मेष, इच्छा, प्रकृति और व्यंग इत्यादि का अुनभव। यह अनुभव हमारी इन्द्रियों के द्वारा हमारे आन्तरिक मन मस्तिष्क में उतर कर हमारी आत्मा को प्रभावित करता है। यह भाव सुख एवं दुख के रूप में हमारे अन्तर्मन में प्रवाहित होता है एवं विभिन्न रूपों में परिस्थितियों वश प्रकट होते है। इन्ही भावों को भारतीय प्राचीन शास्त्रों में रस की कोटि में विभाजित किया गया है। यह रस कलाकार की कृतियों में विभिन्न रूपों में एवं रंगों की मनोहारी उपस्थिति से प्रकट होते है जो दर्शक को आनन्द विभोर करते है।